Three years of muography at Mount Etna: results and perspectives. (1st February 2022) - Gallo, G.; Lo Presti, D.; Bonanno, D.L.; Bonanno, G.; Ferlito, C.; La Rocca, P.; Reito, S.; Riggi, F.; Romeo, G.
Abstract: The summit craters system represents the point of maximum expression of the persistent tectonic activity at Mount Etna volcano. The Muography of Etna Volcano (MEV) project began in 2016 as a pilot project for the successive installation of a permanent muographic observatory. It aims to demonstrate the detector's capability to observe density anomalies inside the volcanic edifice and monitor their time evolution. The first muon telescope built by the collaboration and installed at the base of the North-East crater from August 2017 to October 2019 was already able to get significant results. This work describes the characteristics of the muon-telescope and summarizes the principal outcomes obtained, with a quick look at the current status of the project and future developments.